A comprehensive review on the geomechanical properties of gas hydrate bearing sediments - Lijith, K.P.; Malagar, Bhini.R.C.; Singh, Devendra Narain (Marine and petroleum geology, 2019)
Natural gas hydrates (NGH) that form in sediments beneath the ocean beds are a potential source to meet growing global energy demand. Gas hydrate bearing sediments (GHBS) exhibit improved geomechanical properties (viz., shear strength, stiffness, compressibility, and Poisson's ratio) that are responsible for their greater stability as compared to the native sediments. However, dissociation of gas hydrates during extraction of gas, instability in the GHBS could trigger submarine slope failures, seabed subsidence, and failure of the foundations of seafloor installations. In order to reduce the risk of occurrence of such geohazards, it is imperative to ascertain the stability of GHBS by understanding the variations in their geomechanical properties through field and laboratory investigations, which are time consuming and prohibitively expensive for many researchers. With this in view, the present study attempts to decipher the variation of geomechanical properties with respect to various parameters that affect them (viz., hydrate saturation (SH), hydrate morphology, and confining pressure-temperature conditions), by critically synthesizing the existing data in the literature. It has been noticed that the shear strength and stiffness are the major parameters influencing the stability of GHBS and both share power law relationship with SH. Further, it is noticed that the cohesion is the predominant component of the shear strength of GHBS and shows significant improvement for SH values greater than 15–50%. The variability of cohesion and stiffness with respect to SH have been analysed in tandem with the volumetric deformation, during the shearing process, to propose particle level mechanism hypothesis that provides an insight in to the stress-strain behavior of GHBS. The proposed relationships and mechanisms would aid in understanding the behavior and development of improved modeling of geomechanical properties of GHBS. •A critical review of the geomechanical properties of gas hydrate bearing sediments (GHBS) is conducted with an aim to aid in the modelling of their behaviour during formation and dissociation of hydrates.•Power law relationships for determining cohesion and stiffness of GHBS from hydrate saturation are proposed.•A particle level mechanism that helps in understanding the stress-strain behaviour of GHBS has been proposed.•It is found that the stiffness of GHBS increases linearly, and the shear strength decreases linearly, with confining pressure and hydrate formation temperature, respectively.